Accommodating blind and partially sighted clients. Issue 9 (10th October 2014) - England, Gary; Gebbels, Tim; Whelan, Chantelle; Freeman, Sarah
Abstract : Veterinary surgeons provide an important service to blind and partially sighted guide dog owners. By adopting basic disability awareness and visual impairment training, practices can ensure that the assistance needs of those clients are met, facilitating access to veterinary care.